Collagen scaffold-seeded iTenocytes accelerate the healing and functional recovery of Achilles tendon defects in a rat model - Später, Thomas; Del Rio, Patricia; Shelest, Oksana; Wechsler, Jacob T.; Kaneda, Giselle; Chavez, Melissa; Sheyn, Julia; Yu, Victoria; Metzger, Wolfgang; Huang, Dave; Metzger, Melodie; Tawackoli, Wafa; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Tendon injuries represent an ongoing challenge in clinical practice due to poor regenerative capacity, structure, and biomechanical function recovery of ruptured tendons. This study is focused on the assessment of a novel strategy to repair ruptured Achilles tendons in a Nude rat model using stem cellseeded biomaterial. Specifically, we have used induced pluripotent stem cell (iPSC)-derived mesenchymal stem cells (iMSCs) overexpressing the early tendon marker Scleraxis (SCX, iMSC SCX+ , iTenocytes) in combination with an elastic collagen scaffold. Achilles tendon defects in Nude rat models were created by isolating the tendon and excising 3mm of the midsection. The Achilles tendon defects were then repaired with iTenocyte-seeded scaffolds, unseeded scaffolds, or suture only and compared to native Nude rat tendon tissue using gait analyses, biomechanical testing, histology, and immunohistochemistry. The results show faster functional recovery of gait in iTenocyte-seeded scaffold group comparing to scaffold only and suture only groups. Both iTenocyte-seeded scaffold and scaffold only treatment groups had improved biomechanical properties when compared to suture only treatment group, however no statistically significant difference was found in comparing the cell seeding scaffold an scaffold only group in terms of biomechanical properties. Immunohistochemistry staining further demonstrated that iTenocytes successfully populated the collagen scaffolds and survived 9 weeks after implantation in vivo. Additionally, the repaired tissue of iTenocyte-treated injuries exhibited a more organized structure when compared to tendon defects that were repaired only with